Screening of 154 Veterinary Drug Residues in Foods of Animal Origin Using LC–MS/MS: First Action 2020.04. (22nd December 2020) - Desmarchelier, Aurélien; Bessaire, , Thomas; Savoy, Marie-Claude; Tarres, Adrienne; Mujahid, Claudia; Beck, Andrea; Mottier, Pascal; Delatour, Thierry
Abstract: Background: Veterinary drug residues in food are substances (>200 compounds) exhibiting potential health risks for consumers, thus being regulated in national legislations and the Codex Alimentarius. Most of the compounds are regulated based upon a maximum residue limit (MRL) while a few of them are banned in food for humans. The food sector needs a reliable and consensus analytical platform able to monitor these substances in a wide range of food commodities. Objective: Several confirmatory methods based on liquid chromatography-mass spectrometry are available in the literature for either screening or quantification of veterinary drug residues in food, but usually applicable to limited scope of matrices. The current work describes the single-laboratory validation (SLV) of a method for screening 154 veterinary drug residues in several food categories. Methods: This work describes a streamlined platform making use of liquid chromatography-tandem mass spectrometry (LC-MS/MS) for screening 105 antibiotics, 41 antiparasitics, 5anti-inflammatory agents, and 3 tranquilizers in foods of animal origin. For the best performance across the commodities (dairy-, meat-, fish-, and egg-based materials), four method streams were established. As a screening tool, probabilities of detection (PODs) were assessed at the screening target concentration (STC < MRL) and the blank. Results: The SLV led to PODs at the STC >94% and PODs in the blank < 4%. Conclusion: Performance is in agreement with the acceptance criteria defined in SMPR 2018.010. Highlights: The Expert Review Panel approved the present method as AOAC Official First Action 2020.04 .